Muscle Damage Due to Fusidic Acid–Statin Interaction: Review of 75 Cases From the French Pharmacovigilance Database and Literature Reports. (May 2019) - Bataillard, Maxime; Beyens, Marie-Noëlle; Mounier, Geneviève; Vergnon-Miszczycha, Delphine; Bagheri, Haleh; Cathebras, Pascal
Abstract : Background/Area of Uncertainty: Statins, which reduce cardiovascular risk in both primary and secondary prevention, are one of the most widely prescribed therapeutic classes in the world. Usually well-tolerated, statin-associated muscle symptoms are a well-known adverse effect. Fusidic acid (FA) is a bacteriostatic antibiotic of interest in the treatment of methicillin-resistant Staphylococcus aureus infections. Cases of rhabdomyolysis, sometimes fatal, have been reported after coprescription of FA and a statin. Data Sources/Area of Uncertainty: We studied 75 cases of muscle damage related to interaction between FA and a statin reported in the French national pharmacovigilance database (43 cases) and from a literature review (32 cases). Results: Cases were mostly men (72.5%), often overweight (mean body mass index: 29.4). The most commonly reported statins were atorvastatin (60%), simvastatin (22.7%), and rosuvastatin (8.0%). Muscle disorders appeared on average 30 days after initiation of FA. Symptoms were muscle weakness (82%), dark urine (71%), and myalgia (61%). Mean creatine kinase level at diagnosis was 43, 890 UI/mL, and acute renal injury occurred more than half of the cases. Outcome was fatal in 22% of cases and 28% kept sequelae at the end of the follow-up (54 days). Conclusions: Muscle damage induced by interaction between FA and statin is a potentially life-threatening complication, leading to contraindication of this association in France. This is to be reminded especially because FA is about to get FDA approval and should soon be available in the United States.